Modern ewe-registry and evaluation in meat productive farms - Rajczi, Balázs; Toldi, Gyula; Hornné Temesvári, Erika (Acta Agraria Kaposváriensis, 2006)
Due to the strict individual registry the livestock breeders need to have a simple and quick informatic database, which has considerable improved nowadays. Most of all the sheep farming requires the modernisation since it is the most low-cost branch. The aim of our study was to help in this improvement. A sheep-farm of Zselic was used to establish an easy, useful moreover quite detailed and comprehensive informatical individual registry. To attain my goals a selection index were calculated for the evaluation of the life-long productivity of breeding animals. The breeding values were taken into account in this selection index depended on their importancy for the farmer. It makes the easy and quick and reliable selection of the breeding ewes and their female progenies as well as the culling of law productive ewes. Further informatical development is needed, however this established registry is suitable for the directives of modern ewes registry. To improve the accuracy of the ranging and the selection of the ewes the selection index has to be corrected. This evaluation system can be extended to other farms with even different demands because the account of the breeding values or the number of them are variable.